Nanoprecipitates assisting subsurface cracking in high-strength steel under very high cycle fatigue. (February 2023) - Chen, Yao; Wang, Shijian; Li, Haizhou; Liu, Yongjie; He, Chao; Cui, Jie; Jiang, Qing; Liu, Chang; He, Qiyuan; Liang, Quanwei; Li, Lang; Wang, Qingyuan
Abstract: Subsurface cracking is a common feature at N > 10 7 cycles [i.e., in very high cycle fatigue (VHCF) regime]. Widely reported literatures focus mainly on the subsurface cracking at inclusions. However, it can initiate at the inner matrix as well, and the physic origin remains unclear. Here, we systematically explore the subsurface cracking at the inner matrix from mesoscale to atomic-scale. The results show that the subsurface cracking initiates from a single coarse lath, and dislocation tangles and cells generate at the extremely localized plastic deformation zones in proximity to the nanoprecipitates being of α-Fe. We suggest that the dislocations with high dense are blocked at the nanoprecipitate/α-Fe interfaces resulting in the nucleation of interfacial microcracks, which then coalesce into a trans-granular crack along the sub-boundaries covered by nanoprecipitates, finally the crack initiates within the coarse lath. These findings provide fundamental insights into the mechanism of precipitation-strengthening in anti-fatigue designs. Graphical abstract: Image, graphical abstract